An incidental enterocolic lymphocytic phlebitis pattern is seen commonly in the rectal stump of patients with diversion colitis superimposed on inflammatory bowel disease. Issue 5 (15th January 2009) - Chetty, R; Hafezi, S; Montgomery, E
Abstract : Aims: Enterocolic lymphocytic phlebitis (ELP) is an uncommon cause of bowel pathology and most frequently results in ischaemia. It is characterised by an artery-sparing, venulocentric lymphoid infiltrate that causes a phlebitis and vascular compromise. Rare cases of ELP have been encountered with lymphocytic colitis in the absence of ischaemic bowel change. The present study examined the occurrence of ELP in the setting of diversion colitis and inflammatory bowel disease, as well as in random colectomy specimens. Methods: The study cohort comprised the following: 26 completion proctectomy specimens for ulcerative colitis with superimposed diversion colitis in the rectal stump; 3 colectomy specimens for Crohn disease with diversion colitis; 6 colectomy specimens for adenocarcinoma and/or diverticular disease with diversion colitis; 34 resection specimens with ulcerative colitis only; 19 with Crohn disease only; and 100 random colon resection specimens for adenocarcinoma, adenoma, diverticular disease and ischaemia. Results: ELP was present in 18 of the 26 ulcerative colitis cases with diversion colitis, 3/3 Crohn disease cases with diversion colitis, 1/6 cases of diverticular disease with diversion colitis, 6/34 cases of ulcerative colitis without diversion, 2/19 Crohn disease cases without diversion colitis, and only 1 of 100 colectomy cases without inflammatory bowel disease or diversion colitis. Conclusion: ELP occurs most frequently in cases that have been diverted for inflammatory bowel disease. Fewer cases of ELP were noted in cases of inflammatory bowel disease in the absence of diversion colitis. It is postulated that altered bowel flora and immune dysregulation may be pivotal in the causation of this association.